Vancomycin Induced Eosinophilic Peritonitis, A Case Report - Hooman, Nakysa; Jahangiry, Fariba; Asdaghi, Mina; Ghafari, Leila (Journal of Pediatric Nephrology, 2018)
Drug induced peritonitis is a rare but important complication of CAPD. Hereby, we report a case that developed eosinophilic peritonitis during intraperitoneal administration of vancomycin. With a suspicion of vancomycin-induced eosinophilic peritonitis, vancomycin was discontinued. Antihistamine started and the PD effluent two days after stopping the drug revealed a WBC count of 85/µl (10% Eosinophil, 71% Lymphocytes). Systemic signs improved dramatically in less than a week. In conclusion, drug induced peritonitis should be considered in different diagnosis of each patient on CAPD before considering administering another new antibiotic. Keywords: Vancomycin; Peritonitis; Allergy and Immunology; Child.